Basic schemes of synchronized pulsewidth modulation for cascaded inverters of drive system with two DC-sources - Oleschuk, V.; Sizov, A. (Технічна електродинаміка, 2013)
Continuous and discontinuous schemes of synchronized pulsewidth modulation (PWM) have been applied for control of an open-end winding motor drive fed by cascaded inverters supplied by two dc-sources with non-equal voltages. Simulations illustrate behavior of these systems with algorithms of synchronized PWM. Spectra of multilevel phase voltage of open-end winding motor drives with synchronized PWM do not contain even harmonics and sub-harmonics during the whole control range, which is especially important for the medium-power and high-power systems. Представлены результаты исследования и моделирования режимов работы системы электропривода на базе асинхронного электродвигателя с разомкнутыми обмотками, подключенными к сдвоенным инверторам напряжения с синхронной модуляцией непрерывного и прерывистого типа, питающихся от двух изолированных источников постоянного напряжения. Показано, что в спектре многоуровневого фазного напряжения подобных систем с алгоритмами синхронной широтно-импульсной модуляции на всем диапазоне регулирования отсутствуют четные гармоники и субгармоники, что представляется особенно важным для преобразовательных систем повышенной мощности. Представлено результати дослідження та моделювання режимів роботи системи eлектроприводу на базі асинхронного електродвигуна з розімкненими обмотками, які підключено до подвоєних інверторів напруги з синхронною модуляцією неперервного та пeреривчастого типу, що живляться від двох ізольованих джерел постійного струму. Показано, що у спектрі багаторівневої фазної напруги таких систем з алгоритмами синхронної широтно-імпульсної модуляції у всьому діапазоні регулювання відсутні парні гармоніки та субгармоніки, що є найважливішим для перетворювальних систем підвищеної потужності